A genome-wide RNA interference screen disentangles the Golgi tropism of LC3. Issue 3 (4th March 2021) - Cerrato, Giulia; Kepp, Oliver; Sauvat, Allan; Kroemer, Guido
ABSTRACT: Oleate, the most abundantly occurring cis -unsaturated fatty acid, has the particularity to induce the accumulation of MAP1LC3B/LC3 (microtubule associated protein 1 light chain 3 beta) at the trans -Golgi apparatus. A genome-wide RNA interference screen designed to identify the mechanisms of this LC3 redistribution led to the identification of a BECN1-PIK3C3-independent pathway that, however, requires the ATG12–ATG5 and ATG7-dependent conjugation system, and several genes/proteins involved in endoplasmic reticulum (ER)-to-Golgi anterograde protein transport, as well as the unfolded protein response, including the integrated stress response that results in the phosphorylation of EIF2A/eIF2α (eukaryotic translation initiation factor 2A). Functional experiments revealed that oleate blocks conventional protein secretion, stalling the process at the level of the trans -Golgi network. Oleate-induced blockade of protein secretion occurred even after depletion of ATG5, suggesting that it does not rely on the recruitment of LC3 to the Golgi apparatus (which does require ATG5). Rather, it appears that oleate and other pharmacological inhibitors of protein secretion with a similar mode of action provoke a perturbation of the trans -Golgi compartment that secondarily results in the local enrichment of LC3.